2011
DOI: 10.1007/s10120-011-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the new (7th) UICC N classification in the prognosis evaluation of gastric cancer patients: a comparative study between the 5th/6th and 7th UICC N classification

Abstract: Background The most important prognostic factor after curative surgery for gastric carcinoma is the presence of lymph node metastases. According to the 7th edition of the UICC TNM staging system for gastric cancer, N classification was categorized as N0 (no regional lymph node metastasis), N1 (1-2 regional lymph node metastases), N2 (3-6 regional lymph node metastases), and N3 (7 or more regional lymph node metastases). The purpose of this study was to evaluate the rationality of the new UICC/AJCC N classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 25 publications
(31 reference statements)
2
56
0
1
Order By: Relevance
“…Another study from Korea showed similar results for the new TNM system, proving a more detailed prognostic assessment, especially between T2 and T3 and N1 and N2 tumors [2]. The advantage of the new (7th) edition was mainly confirmed for the prognostic value of accurate lymph node assessment [3].…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Another study from Korea showed similar results for the new TNM system, proving a more detailed prognostic assessment, especially between T2 and T3 and N1 and N2 tumors [2]. The advantage of the new (7th) edition was mainly confirmed for the prognostic value of accurate lymph node assessment [3].…”
mentioning
confidence: 66%
“…Another study from Korea showed similar results for the new TNM system, proving a more detailed prognostic assessment, especially between T2 and T3 and N1 and N2 tumors [2]. The advantage of the new (7th) edition was mainly confirmed for the prognostic value of accurate lymph node assessment [3].Concerning the classification of early gastric cancer (GC) in the new system, a study from Italy confirmed the usefulness of the new classification for metastatic lymph nodes as a prognostic tool in case of early GC. …”
mentioning
confidence: 67%
“…It seems that there should be a compensation for this problem. There was a significant difference in the 5-year survival rate between the 7 th N3a and N3b (Ichikura et al, 1999;Chae et al, 2011). As several data indicated there was a significant difference in survivals between N2 and N3 in the 6 th N classification (Ichikura et al, 1999;).…”
Section: Discussionmentioning
confidence: 86%
“…The revision of the pN classification for the 7 th TNM classification will be more conspicuous and needs to be fully discussed Chae et al, 2011;Jung et al, 2011). An ideal lymph node staging system for gastric cancer has been controversial and has changed whenever a revision in the TNM classification has been made (Klein et al, 2001;Yamashita et al, 2008;Jung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation